Evaluation of Participant Patient Satisfaction Evaluation in Childbirth Care at Independent Midwifery Practices - Dwie Ayu (Alma Ata University Press, 2020)
Patient satisfaction is a measure of the quality of care. One important problem that continues to be faced is the lack of good quality service and getting client satisfaction. The aim is to explore the satisfaction of maternity patients using BPJS guarantees for the services provided by midwives in the Midwife's Independent Practice. This research method uses qualitative short narrative or force. PubMed and Proquest searches were carried out systematically from 2008 to 2018. Quality articles were selected based on inclusion and Critical Assessment criteria. Based on the review found k Mothers' satisfaction with prenatal care can be said to be the experience that results from subjective judgments about what the mother expects and what actually happens related to labor. Factors that influence patient satisfaction in labor are environmental factors, technical and professional aspects of nursing, and aspects of care and communication. Quality of service is the dominant concept in quality assurance and quality improvement programs in the health sector. One method for determining quality is evaluating customer satisfaction. One tool for evaluating and analyzing service quality gaps is SERVQUAL to study the difference between customer expectations and perceptions in different dimensions including in five dimensions of service quality namely physical evidence, service reliability, responding, assurance and empathy. To get health services, you can use health insurance (BPJS). The benefits of health insurance are freeing participants from the difficulty of providing cash, health costs can be monitored, quality of service can be overcome and the availability of health data.